2017
DOI: 10.3126/jie.v12i1.16906
|View full text |Cite
|
Sign up to set email alerts
|

Importance of English in Engineering for Professional Communication: A Study in the Nepalese Context

Abstract: Abstract:This article attempts to highlight the importance of English in the professional communication in the field of engineering in Nepal. The main objective of the article is to shed light on the role English language plays in the communication related to engineering. Based primarily on the review of some relevant literature available, the present article reveals the fact that English being one of the global languages used in a wide range of communicative fields all over the world, it serves as an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…English language instruction (ELT) is becoming more and more popular throughout the world, in both developed and developing nations (Aryal et al, 2016). Some of the studies like (Shrestha et al, 2016; demonstrated that English is highly valued in official communication in Nepal and has a prominent role in journalism, research, technology, and education. Actually, the students who went to the best English-medium schools were able to perform better academically and had more career opportunities due to their high level of language competence (Ghimire, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…English language instruction (ELT) is becoming more and more popular throughout the world, in both developed and developing nations (Aryal et al, 2016). Some of the studies like (Shrestha et al, 2016; demonstrated that English is highly valued in official communication in Nepal and has a prominent role in journalism, research, technology, and education. Actually, the students who went to the best English-medium schools were able to perform better academically and had more career opportunities due to their high level of language competence (Ghimire, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of such affiliations from different international universities, the horizon of the English language in Nepal is increasing day by day, and students are persuaded to have good command over the English language. Similarly, Shrestha et al, (2016) advocated that English is a must in the field of engineering since most of the subjects are taught in the English language and the examinations are conducted in the English language as well. In the same way, for measuring proficiency in English, a practical examination of 25 marks is taken which measures students' listening and speaking ability.…”
Section: Role Of English In Higher Education In Nepalmentioning
confidence: 99%
“…Likewise, after the membership of Nepal with various international organizations such as the World Trade Organization, the World Bank, and the United Nations Organization, several multinational companies and international non-government organizations are established and they have created job opportunities to Nepalese who are competent in English along with skills required to perform the job (Onta, 2003). Moreover, English has a very significant status in official use as a means of communication in the Nepali scenario as well as it has an important place in journalism, education, science, and technology (Shrestha et al, 2016). The reality is that the children who attended good English-medium schools had acquired a high-level of linguistic proficiency which facilitated academic performance and opened higher possibilities for the jobs (Sah & Li, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Language proficiency offers exceptional advantages for foreign learners in terms of their abilities to either work abroad or in their own country (Rajprasit & Hemchua, 2015). Good language skills are required for successful social interaction (Shrestha, Pahari, & Awasthi, 2017;Louhiala-Salminen & Kankaanranta, 2011). The experiential-tutorial strategies for language learning also aided in improving the communicative competence of language learners (Bloom & Gascoigne, 2017).…”
Section: Experiential-tutorial Learning In Indonesian Learning For Fomentioning
confidence: 99%